2018
DOI: 10.1016/j.bbrc.2017.11.071
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PiT-2 results in abnormal bone development and decreased bone mineral density and length in mice

Abstract: Normal bone mineralization requires phosphate oversaturation in bone matrix vesicles, as well as normal regulation of phosphate metabolism via the interplay among bone, intestine, and kidney. In turn, derangement of phosphate metabolism greatly affects bone function and structure. The type III sodium-dependent phosphate transporters, PiT-1 and PiT-2, are believed to be important in tissue phosphate metabolism and physiological bone formation, but their requirement and molecular roles in bone remain poorly inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
1
15
1
Order By: Relevance
“…Extraskeletal abnormalities in Slc20a2 knockout mice recapitulate the autosomal dominant human condition of PFBC characterized by symmetric calcification in the basal ganglia and other brain regions in affected heterozygous individuals. However, the major dental, skeletal, and ocular abnormalities reported here were not recognized previously and result from complete SLC20A2 deficiency. Thus, SLC20A2 deficiency causes abnormalities of endochondral and intramembranous ossification that affect skeletal development, linear growth, and mineral accrual, resulting in profound and discordant decreases in bone strength and stiffness.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Extraskeletal abnormalities in Slc20a2 knockout mice recapitulate the autosomal dominant human condition of PFBC characterized by symmetric calcification in the basal ganglia and other brain regions in affected heterozygous individuals. However, the major dental, skeletal, and ocular abnormalities reported here were not recognized previously and result from complete SLC20A2 deficiency. Thus, SLC20A2 deficiency causes abnormalities of endochondral and intramembranous ossification that affect skeletal development, linear growth, and mineral accrual, resulting in profound and discordant decreases in bone strength and stiffness.…”
Section: Discussioncontrasting
confidence: 52%
“…This phenotype is recapitulated in SLC20A2‐deficient mice, in which a local increase in Pi concentrations in the cerebrospinal fluid (CSF) has been suggested to contribute to Ca‐Pi deposition in CSF‐producing tissues and microvessels . Preliminary histomorphometric analysis of SLC20A2‐deficient mice also suggested a role for SLC20A2 in skeletal mineralization, whereas SLC20A2 expression in vascular smooth muscle has been proposed to inhibit vascular calcification …”
Section: Introductionmentioning
confidence: 98%
“…18,19 It is recently reported that PiT-2 may play a role in bone development and its deletion leads to decreased MBD. 20 However, in fact, no toxicological effects in lung, brain, or bone were observed in rats and dogs on EOS789 in repeated oral dose toxicity studies lasting up to 13 weeks (data not shown). Even though the systemic inhibition of NaPi-IIb and PiT-2 has a potential risk of ectopic calcification and decreased bone mineral density, EOS789 is expected to avoid these safety risks due to its very low fractional absorption.…”
Section: Discussionmentioning
confidence: 93%
“…(2)(3)(4) In contrast, we and others have rather shown the involvement of PiT2 in these phenomena in vivo. (5,6) Therefore, when considering the recent in vivo studies rather than early in vitro observations, the absence of identified mutations in the PiT1 gene in PFBC patients does not appear surprising.…”
Section: To the Editormentioning
confidence: 99%